Different psychophysiological responses to a high-intensity repetition session performed alone or in a group by elite middle-distance runners. Issue 8 (14th September 2019) - Casado, Arturo; Moreno-Pérez, Diego; Larrosa, Mar; Renfree, Andrew
Abstract: Internal training load refers to the degree of disturbance in psychophysiological homeostasis provoked by a training session and has been traditionally measured through session-RPE, which is the product of the session Rate of Perceived Exertion (RPE) and the duration. External training load refers to the actual physical work completed, and depends on session volume, intensity, frequency and density. Drafting, which is achieved by running closely behind another runner has been demonstrated to reduce the energy cost of running at a fixed speed and to improve performance. Therefore, it is hypothesised that psychophysiological responses might reflect different levels of internal load if training is performed individually or collectively. 16 elite middle-distance runners performed two high-intensity training sessions consisting of 4 repetitions of 500 m separated by 3 min of passive recovery. Sessions were performed individually and collectively. Times for each repetition, RPE, core affect (valence and felt arousal) and blood lactate concentrations [BLa] were measured after each repetition. Main time effect was significant and increased across repetitions for [BLa] and RPE ( p  < 0.001), and decreased for valence ( p  = 0.001). Main group effect was significant and values were higher when training individually for [BLa] ( p  = 0.003) and RPE ( p  = 0.001), and lower for valence ( p  = 0.001). No differential responses were found between conditions in terms of repeat time or felt arousal. Findings demonstrate that elite middle-distance athletes running collectively display lower levels of internal training load compared to running alone, despite external training load being similar.